PENINGKATAN KARAKTER SISWA PADA PENERAPAN PERANGKAT PEMBELAJARAN SAINS BERBASIS HUMANISTIS - Sudarto, Sudarto (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2022)
This research was an pre-experimental study with a One-Shot Case Study research design which aimed to determine the level of achievement of adding student character items through the application of Humanistic Science-Based Learning Devices. The research population was all students of class VII SMPN 24 Makassar. The sampling method was a Simple Random Sampling. The research data were obtained using a non-test instrument in the form of a questionnaire. The data analysis technique used was a descriptive statistical techniqu. The results showed that the students who had been able to develop six character items were 3 people (10%), 5 character items were 7 people (23.33%), 4 character items were 10 people (33.33%), 3 characters were 8 people (26.67%), and 2 character items totaling 2 people (6.67%). Conclusion: All students have experienced an optimal increase in character because they have achieved a minimum of two character growth items as indicators of optimalization of character growth.